Penguatan Peran Perawat Dalam Pelaksanaan Asuhan Keperawatan Melalui Pelatihan Layanan Prima - Simamora, Roymond H; Purba, Jenni Marlindawani; Bukit, Evi Karota (LPPM UNINUS, 2018)
Community Service aims to enable nurses to understand the concept of service (the importance of service) for the survival of the hospital business. Nurses are able to see service from the point of view of the customer (patient) and understand Nine Service Bites